Liability : perspectives and policy - Litan, Robert E.; Winston, Clifford (Washington, D.C. : Brookings Institution, 1988)
State and federal courts have been flooded with litigation. At the same time, premiums for liability insurance have risen steeply. These developments have threatened the functioning of the entire civil litigation process and touched off a national debate over what should be done. In this book, a team of economists and lawyers evaluate the issues underlying this debate and suggest policies to ameliorate the problems of both the courts and the insurance industry. They examine the functions of tort law in providing compensation and deterring harmful behavior, the apparent liberalization of tort doctrines.
Includes bibliographical references and index.
ne 25/01/2019
Loans
Keywords: Liability (Law).; Liability insurance; Torts